Sosialisasi dan Pelatihan Kolaboratif Remaja-Keluarga untuk Membangun Generasi Unggul di Kecamatan Parangloe (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
This Community Service Program (PKM) aims to improve the quality of youth and strengthen the role of families in youth development through structured socialization and training programs in Parangloe District, Gowa Regency, South Sulawesi. The formation of an excellent generation requires active and synergistic roles among youth, families, and the social environment. Families hold a strategic position as the primary space for character formation, while youth need proper guidance to develop their potential optimally and responsibly. The program was implemented through a series of socialization activities, seminars, interactive discussions, and training sessions involving youth, families, community leaders, sub-district government officials, and facilitators from educational institutions. Through a collaborative socialization and training approach, the activities successfully enhanced participants’ understanding of the importance of effective communication, positive parenting, and the strengthening of character values within family life. The results indicate increased participant knowledge regarding the roles of youth and families, the establishment of supportive collaboration, and the growth of commitment to creating a conducive environment for youth development. This program represents an important step in preparing a generation in Parangloe District that is strong in character, adaptive, competitive, and capable of contributing positively to future community development.